Vegetable proteins as potential encapsulation agents : a review (2018)
ABSTRACT: Proteins from plant sources are macromolecules of industrial interest due to its high availability, biodegradability, renewable character and functional properties such as biocompatibility, good amphiphilic properties, water solubility, foaming, emulsifying, gelling and film-forming abilities. In this scenario, these macromolecules have a high applicability in various emulsification stabilization processes, and have a potential use as a wall-forming material for the encapsulation processes of active ingredients. Currently, proteins extracted from soybean, pea, sunflower, rice and wheat seeds have already been studied as versatile stabilizers and emulsion coatings by coacervation and encapsulation processes by spray-drying. However, the capsule-forming ability of these macromolecules is enhanced by physical, chemical or enzymatic changes in their structure, favoring the interactions with the core material, the solvent, and increase of the encapsulation efficiency and its versatility in other encapsulation techniques.